High-permeability high-temperature-resistant ultralow-emission filter material
By adopting a multi-layer structure filter material design, combining alumina fibers, silicon carbide fibers, zirconium titanate and other materials, adding nanoparticles and activated carbon layers, and setting up a wire mesh, the problem of high-temperature waste gas treatment in the existing technology is difficult to take into account both breathability, high temperature resistance and low emissions, and achieving efficient waste gas filtration effect.
Patent Information
- Application Number
- CN202510147693.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When dealing with high-temperature exhaust gas, it is difficult to take into account high breathability, high temperature resistance and ultra-low emissions, and it is usually necessary to make a trade-off between breathability and high temperature resistance.
A filter material design is adopted with a multi-layer structure, in which the first layer uses alumina fibers, silicon carbide fibers, zirconium titanate or foam ceramic materials, the second layer adds nanoparticles to the first layer of ceramic fibers to improve breathability and capture efficiency, the third layer is equipped with a high-efficiency activated carbon filter layer to adsorb volatile organic matter, and a wire mesh is arranged between the second and third layers to enhance structural strength.
It achieves compatibility of high breathability, high temperature resistance and ultra-low emissions, improves the overall performance of the filter material, and can effectively remove particulate matter and harmful substances in high-temperature exhaust gas.
Smart Images

Figure CN119869093A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of filter materials, and in particular relates to a highly air-permeable, high-temperature-resistant and ultra-low-emission filter material. Background Art
[0002] Filter material is a material used to filter and separate impurities or solid particles. It can remove impurities, particulate matter and suspended matter from liquids or gases to make them purer and cleaner. It is widely used in various industries, such as chemical industry, environmental protection, food processing, medicine, etc., to achieve the goals of purification, filtration, separation and protection, thereby improving product quality, protecting equipment and systems, and reducing pollution to the environment. For example, in industrial production, filter materials can prevent solid particles and pollutants from entering equipment and systems, reduce wear, blockage and failure of equipment, and extend the service life of equipment. In the manufacturing process, filter materials can remove impurities and particulate matter to ensure that the quality and performance of products meet the requirements. In the fields of wastewater treatment, waste gas treatment and environmental governance, filter materials can help remove harmful substances and pollutants and reduce emissions and pollution to the environment. In scientific research and laboratories, filter materials can be used to separate, purify and concentrate samples for further analysis and research.
[0003] When treating high-temperature exhaust gas, high air permeability and high temperature resistance are required. However, the problem with the existing technology is that achieving high air permeability usually requires a large porosity and surface area, which may increase the openness of the material structure and reduce the high temperature resistance. In order to achieve low emission requirements, it may be necessary to use a denser filter material structure to prevent the leakage and diffusion of particulate matter. However, a dense filter material structure may reduce the air permeability, thereby affecting the realization of high air permeability. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a highly air-permeable, high-temperature-resistant and ultra-low-emission filter material, which has the advantages of high air-permeability, high-temperature resistance and ultra-low emission compatibility, and solves the problems of the prior art.
[0005] The present invention is achieved by providing a highly air-permeable, high-temperature-resistant and ultra-low-emission filter material, comprising: First layer: at least one of alumina fiber, silicon carbide fiber, zirconium titanate, and foam ceramic as the first layer filter material; Second layer: nanoparticles are added to the first layer of ceramic fibers; The third layer: a high-efficiency activated carbon filter layer is provided on top of the second layer; A steel wire mesh is arranged between the second layer and the third layer.
[0006] As a preferred method of the present invention, the preparation method of the highly air-permeable, high-temperature-resistant and ultra-low-emission filter material comprises: Step S1, preparing a first layer of filter material: selecting at least one material selected from alumina fiber, silicon carbide fiber, zirconium titanate or foam ceramic as the first layer of filter material, and using a spray molding process to prepare a first layer of filter material having a certain thickness and an appropriate shape according to the selected material; Step S2, preparing the second layer of filter material: using a dipping or spraying method to evenly cover the surface of the first layer of filter material with nanoparticles, and controlling the amount and distribution of the nanoparticles added to increase the surface area and porosity of the filter material, thereby improving the air permeability and capture efficiency; Step S3, laying a steel wire mesh: placing the steel wire mesh on the surface of the second layer of filter material and ensuring that it is tightly combined with the filter material; Step S4, preparing the third layer of filter material: using coating or impregnation to cover the surface of the second layer of filter material with activated carbon material, ensuring that the activated carbon layer is evenly and densely distributed on the second layer of filter material to provide excellent adsorption capacity.
[0007] As a preferred embodiment of the present invention, the first layer is a composite layer, and organic glue or inorganic adhesive is provided between the composite layers for bonding, and the organic glue or inorganic adhesive is arranged in a grid type.
[0008] As a preferred embodiment of the present invention, the first layer: the refractory ceramic fiber of the ceramic fiber filter material is alumina fiber with a thickness of 5-10 mm; The second layer: the nanoparticles of the nanoparticle filter material are silicon dioxide and / or titanium dioxide particles; the nanoparticles are 50 nanometers and have a thickness of 3-5 mm; The third layer: The thickness of the high-efficiency activated carbon material of the high-efficiency activated carbon filter layer is 5-10mm, and the adsorption capacity is greater than 90% of the volatile organic compound adsorption efficiency.
[0009] As a preferred embodiment of the present invention, the mesh size of the steel wire mesh is 2mm x 2mm, the thickness of the steel wire mesh is 0.5-0.8 mm, and the tensile strength of the steel wire mesh is 300MPa-2000MPa.
[0010] As a preferred embodiment of the present invention, a performance enhancement layer is provided between the second layer and the iron wire mesh, and the performance enhancement layer is a carbon fiber layer.
[0011] As preferred embodiment of the present invention, the thickness of the carbon fiber layer is 0.8mm-6mm, the density of the carbon fiber is 1.5-2.0g / cm³, and the tensile strength is 1000-7000MPa, which enables the carbon fiber layer to increase the pressure resistance and wear resistance of the filter material.
[0012] As a preferred embodiment of the present invention, a microporous membrane filtration layer is provided on the activated carbon filtration layer.
[0013] As preferred embodiment of the present invention, the microporous membrane material of the microporous membrane filtration layer is polyimide and / or PTFE, with a thickness of 0.2 mm and a pore size of 0.1 micron.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses at least one of alumina fiber, silicon carbide fiber, zirconium titanate, and foam ceramic as the first layer of filter material to improve the high temperature resistance of the filter material. Nanoparticles are added to the first layer of ceramic fibers to increase the surface area and porosity of the filter material, improve the air permeability and capture efficiency; a high-efficiency activated carbon filter layer is provided on the second layer. Activated carbon has excellent adsorption capacity and can effectively capture and remove volatile organic compounds and reduce their emissions to the environment; a steel wire mesh is provided between the second layer and the third layer to strengthen the structural strength of the filter material and improve its heat resistance. Through this arrangement, high air permeability, high temperature resistance, and ultra-low emission compatibility can be achieved, thereby improving the performance of the filter material. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 2 is a schematic diagram of the structure of a highly air-permeable, high-temperature-resistant and ultra-low-emission filter material provided in Example 1 of the present invention; Figure 2 2 is a schematic diagram of the structure of a highly air-permeable, high-temperature-resistant and ultra-low-emission filter material provided in Example 2 of the present invention; Figure 3 It is a schematic diagram of the structure of the highly air-permeable, high-temperature-resistant and ultra-low-emission filter material provided in Example 3 of the present invention. DETAILED DESCRIPTION
[0016] In order to further understand the content, features and effects of the present invention, the following embodiments are given as examples and described in detail with reference to the accompanying drawings.
[0017] The structure of the present invention is described in detail below in conjunction with the accompanying drawings. Example
[0018] An embodiment of the present invention provides a highly air-permeable, high-temperature-resistant and ultra-low-emission filter material, comprising: First layer 1: at least one of alumina fiber, silicon carbide fiber, zirconium titanate, and foam ceramic is used as the first layer 1 filter material to improve the high temperature resistance of the filter material.
[0019] Second layer 2: Nanoparticles (such as silicon dioxide, titanium dioxide, etc.) are added to the ceramic fibers of the first layer 1 to increase the surface area and porosity of the filter material, thereby improving the air permeability and capture efficiency; The third layer 3: A high-efficiency activated carbon filter layer is provided on top of the second layer 2. Activated carbon has excellent adsorption capacity and can effectively capture and remove volatile organic compounds (VOCs), reducing their emissions to the environment; A steel wire mesh 4 is provided between the second layer 2 and the third layer 3 to strengthen the structural strength of the filter material and improve its temperature resistance.
[0020] Alumina Fiber has good high temperature resistance and chemical stability. It can be used in high temperature filtration applications, providing high air permeability and corrosion resistance. Silicon Carbide Fiber has excellent high temperature tolerance and mechanical strength. It performs well in high temperature environments and can provide good air permeability and corrosion resistance. Zirconia Toughened Alumina (ZTA) is a composite material that improves its mechanical properties and toughness by adding zirconium titanate particles to an alumina matrix. ZTA has high high temperature resistance and good air permeability.
[0021] Foam Ceramic: Foam Ceramic is a porous material with a large number of interconnected pore structures. It can provide good air permeability and has high temperature resistance to a certain extent.
[0022] Through this setting, compatibility with high air permeability, high temperature resistance and ultra-low emissions can be achieved, thereby improving the performance of the filter material.
[0023] Specifically, the preparation method of the highly air-permeable, high-temperature-resistant and ultra-low-emission filter material includes: Step S1, preparing the first layer 1 filter material: selecting at least one material selected from alumina fiber, silicon carbide fiber, zirconium titanate or foam ceramic as the first layer 1 filter material, and using a spray molding process to prepare the first layer 1 filter material having a certain thickness and an appropriate shape according to the selected material; Step S2, preparing the second layer 2 filter material: using the dipping or spraying method to evenly cover the nanoparticles on the surface of the first layer 1 filter material, controlling the amount and distribution of the nanoparticles added to increase the surface area and porosity of the filter material, and improving the air permeability and capture efficiency.
[0024] Step S3, laying the steel wire mesh 4: placing the steel wire mesh 4 on the surface of the second layer 2 filter material and ensuring that it is tightly combined with the filter material; Step S4, preparing the third layer 3 filter material: using coating or impregnation to cover the surface of the second layer 2 filter material with activated carbon material, ensuring that the activated carbon layer is evenly and densely distributed on the second layer 2 filter material to provide excellent adsorption capacity.
[0025] Preferably, the first layer 1 is a composite layer, and organic glue or inorganic binder is provided between the composite layers for bonding. The organic glue or inorganic binder is arranged in a grid type to enhance air permeability.
[0026] The composite layer is made of one or more materials selected from alumina fiber, silicon carbide fiber, zirconium titanate, and foam ceramic. Using the composite layer as the first layer of filter material has the following advantages: 1. Comprehensive performance optimization: The composite layer combines the characteristics and advantages of multiple materials and can be optimized for different requirements. By combining different materials, multiple performance indicators can be improved in a single layer.
[0027] 2. Enhanced high temperature resistance: The composite layer can be made of high temperature resistant materials, such as alumina fiber, silicon carbide fiber and zirconium titanate, to improve the high temperature resistance of the filter material. Refractory ceramic fiber can also be used as part of the composite layer to further enhance the high temperature resistance.
[0028] 3. Improved filtration efficiency: The composite layer can increase the surface area and porosity of the filter media by introducing additives such as nanoparticles into the filter media structure, thereby improving filtration efficiency and capture efficiency. This helps to effectively remove tiny particles and suspended solids.
[0029] 4. Enhanced mechanical properties: Different materials in the composite layer can complement each other to provide better mechanical properties, such as pressure resistance and wear resistance. For example, the carbon fiber layer 5 can be used to enhance the pressure resistance and wear resistance of the filter material.
[0030] 5. Improve the stability of the filter media: The composite layer can increase the stability and durability of the filter media and resist the influence of external environmental factors. This helps to extend the service life of the filter media and improve its long-term performance stability.
[0031] Exemplarily, the first layer 1: the refractory ceramic fiber of the ceramic fiber filter material is alumina fiber with a thickness of 5-10 mm; Second layer 2: The nanoparticles of the nanoparticle filter material are silicon dioxide and / or titanium dioxide particles; the nanoparticles are 50 nanometers and have a thickness of 3-5 mm; The third layer 3: The thickness of the high-efficiency activated carbon material of the high-efficiency activated carbon filter layer is 5-10mm, and the adsorption capacity is greater than 90% of the volatile organic compounds (VOCs) adsorption efficiency.
[0032] Exemplarily, the mesh size of the steel wire mesh 4 is 2 mm x 2 mm, the thickness of the steel wire mesh 4 is 0.5-0.8 mm, and the tensile strength of the steel wire mesh 4 is 300 MPa-2000 MPa.
[0033] Strengthen the structural strength of the filter material and improve its temperature resistance without affecting its air permeability. Example
[0034] Different from Example 1, a performance enhancement layer is provided between the second layer 2 and the iron wire mesh, and the performance enhancement layer is a carbon fiber layer 5, so as to improve the pressure resistance and wear resistance of the filter material and improve its mechanical properties.
[0035] Carbon fiber is a lightweight, high-strength fiber material that can have better pressure resistance and wear resistance after special treatment.
[0036] Specifically, the thickness of the carbon fiber layer 5 is 0.8 mm to 6 mm, the density of the carbon fiber is 1.5 to 2.0 g / cm³, which is conducive to improving the lightweight performance of the filter material, and the tensile strength is 1000 to 7000 MPa, so that the carbon fiber layer 5 can increase the pressure resistance and wear resistance of the filter material. The carbon fiber can exist in the form of yarn, cloth or fiber felt. According to needs, a suitable carbon fiber morphology can be selected to prepare the carbon fiber layer 5. Example
[0037] The following contents are added on the basis of Example 1 or Example 2: A microporous membrane filter layer 6 is arranged on the activated carbon filter layer. The microporous membrane can filter minute particles and solid pollutants in detail, provide higher filtering efficiency, and prevent the activated carbon particles from falling off.
[0038] The microporous membrane material of the microporous membrane filtration layer 6 is polyimide and / or PTFE, with a thickness of 0.2 mm, a pore size of 0.1 micron, and a filtration efficiency of more than 99% for tiny particles and solid pollutants.
[0039] Effect detection: The weight of the filtered filter material is tested to evaluate the filtering effect of the filter material on the exhaust gas as follows: 1. Preparation: Use appropriate tools and equipment, such as electronic balances or weighing machines, and ensure their accuracy and reliability.
[0040] 2. Collect samples: Take out the filtered filter media from the experimental device and perform appropriate treatment (such as drying) to remove moisture or other substances attached to the filter media.
[0041] 3. Weighing: Place the treated filter material on the scale and record its weight. Ensure accurate readings on the scale and be careful to avoid external factors that may affect the results (such as fans, vibrations, etc.).
[0042] 4. Filtration: Make 100m³ of boiler combustion exhaust gas pass through the filter material; 5. Analyze data: Based on the collected weight data, the weight difference before and after the filter can be calculated to evaluate the filter's efficiency in capturing particles in the exhaust gas. By comparing the weight difference, the degree of particle removal by the filter can be determined.
[0043] It can be seen that the filtering effects of Example 1 and Example 2 are similar, and the filtering effect of Example 3 is the best.
[0044] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0045] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A highly air permeable, high temperature resistant and ultra-low emission filter material, characterized in that: include: First layer (1): at least one of alumina fiber, silicon carbide fiber, zirconium titanate, and foam ceramic as the first layer (1) filter material; Second layer (2): nanoparticles added to the ceramic fibers of the first layer (1); The third layer (3): a high-efficiency activated carbon filter layer is provided on the second layer (2); A steel wire mesh (4) is provided between the second layer (2) and the third layer (3).
2. A highly air-permeable, high-temperature-resistant and ultra-low-emission filter material as claimed in claim 1, characterized in that: The preparation method of the highly air permeable, high temperature resistant and ultra-low emission filter material comprises: Step S1, preparing the first layer (1) of filter material: selecting at least one material selected from alumina fiber, silicon carbide fiber, zirconium titanate or foam ceramic as the first layer (1) of filter material, and using a spray molding process to prepare the first layer (1) of filter material having a certain thickness and a suitable shape according to the selected material; Step S2, preparing the second layer (2) of filter material: using a dipping or spraying method to evenly cover the surface of the first layer (1) of filter material with nanoparticles, and controlling the amount and distribution of the nanoparticles added to increase the surface area and porosity of the filter material, thereby improving the air permeability and capture efficiency; Step S3, laying the steel wire mesh (4): placing the steel wire mesh (4) on the surface of the second layer (2) of filter material and ensuring that it is tightly bonded to the filter material; Step S4, preparing the third layer (3) of filter material: using coating or impregnation to cover the surface of the second layer (2) of filter material with activated carbon material, ensuring that the activated carbon layer is evenly and densely distributed on the second layer (2) of filter material to provide excellent adsorption capacity.
3. A highly air-permeable, high-temperature-resistant and ultra-low-emission filter material as claimed in claim 1, characterized in that: The first layer (1) is a composite layer, and organic glue or inorganic adhesive is provided between the composite layers for bonding, and the organic glue or inorganic adhesive is arranged in a grid type.
4. A highly air-permeable, high-temperature-resistant and ultra-low-emission filter material as claimed in claim 1, characterized in that: First layer (1): The refractory ceramic fiber of the ceramic fiber filter material is alumina fiber with a thickness of 5-10 mm; The second layer (2): the nanoparticles of the nanoparticle filter material are silicon dioxide and / or titanium dioxide particles; the nanoparticles are 50 nanometers and have a thickness of 3-5 mm; The third layer (3): The high-efficiency activated carbon filter layer has a thickness of 5-10 mm and an adsorption capacity of more than 90% of volatile organic compounds.
5. The highly air-permeable, high-temperature-resistant and ultra-low-emission filter material according to claim 1, characterized in that: The mesh size of the steel wire mesh (4) is 2 mm x 2 mm, the thickness of the steel wire mesh (4) is 0.5-0.8 mm, and the tensile strength of the steel wire mesh (4) is 300 MPa-2000 MPa.
6. A highly air-permeable, high-temperature-resistant and ultra-low-emission filter material as claimed in claim 1, characterized in that: A performance enhancement layer is provided between the second layer (2) and the iron wire mesh, and the performance enhancement layer is a carbon fiber layer (5).
7. A highly air-permeable, high-temperature-resistant and ultra-low-emission filter material as claimed in claim 6, characterized in that: The thickness of the carbon fiber layer (5) is 0.8 mm to 6 mm, the density of the carbon fiber is 1.5 to 2.0 g / cm³, and the tensile strength is 1000 to 7000 MPa, so that the carbon fiber layer (5) can increase the pressure resistance and wear resistance of the filter material.
8. A highly air-permeable, high-temperature-resistant and ultra-low-emission filter material as claimed in claim 1 or 6, characterized in that: A microporous membrane filtration layer (6) is provided on the activated carbon filtration layer.
9. A highly air-permeable, high-temperature-resistant and ultra-low-emission filter material as claimed in claim 8, characterized in that: The microporous membrane material of the microporous membrane filtration layer (6) is polyimide and / or PTFE, with a thickness of 0.2 mm and a pore size of 0.1 micrometer.
Citation Information
Patent Citations
Preparation method of multilayer-structure nano fiber composite membrane for filtering particulates in air
CN106541683A
Environmental protection device for removing industrial exhaust gas and dust
CN108554161A
Needling filter material with good oil absorbency
CN117227264A
Filter element for air purification
CN211158905U
Air purifier filter core
CN212214966U